2006
DOI: 10.1007/s00221-006-0439-1
|View full text |Cite
|
Sign up to set email alerts
|

Experimental manipulations of the subthalamic nucleus fail to suppress tonic seizures in the electroshock model of epilepsy

Abstract: Recently, it has been shown that the subthalamic nucleus (STN) has anticonvulsant effects on epileptic seizures originating from the forebrain. The aim of the present study was to determine whether the anticonvulsant properties of the STN extend to the suppression of tonic seizures originating from the brainstem elicited by electroshock in rats. Three different procedures were used to manipulate activity in the STN and in each case the duration of tonic hindlimb extension elicited by electroshock was used as a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 36 publications
1
7
0
Order By: Relevance
“…In the present case of injections of NMDA and muscimol failing to elicit similar anticonvulsant effects, it is proper to consider whether appropriate doses and an optimal delay before testing were used. Firstly, in the present study the drug doses were similar to those reported by other investigators (Kinjo et al, 1990;Depaulis et al, 1994;Dybdal & Gale, 2000;Shehab et al, 2006). Secondly, in pilot investigations to establish appropriate drug dosages for the present study, larger doses of NMDA (10 mm) and muscimol (200-400 pmol) resulted in the death of most subjects tested.…”
Section: Increasedsupporting
confidence: 76%
“…In the present case of injections of NMDA and muscimol failing to elicit similar anticonvulsant effects, it is proper to consider whether appropriate doses and an optimal delay before testing were used. Firstly, in the present study the drug doses were similar to those reported by other investigators (Kinjo et al, 1990;Depaulis et al, 1994;Dybdal & Gale, 2000;Shehab et al, 2006). Secondly, in pilot investigations to establish appropriate drug dosages for the present study, larger doses of NMDA (10 mm) and muscimol (200-400 pmol) resulted in the death of most subjects tested.…”
Section: Increasedsupporting
confidence: 76%
“…Smaller projections arriving from brainstem areas of substantia nigra, pendunculopontine nucleus, and raphe nuclei bring dopaminergic, cholinergic, and serotonergic activity that modulates STN activity (Hamani et al., 2004). Microinfusion of muscimol into STN raises the threshold for seizures in some, but not all animal models (Veliskova et al., 1996; Shehab et al., 2006). Electrical stimulation of the STN in rodents, and humans, raises the seizure threshold and has an anticonvulsant effect (Chabardes et al., 2002; Lado et al., 2003).…”
Section: Mechanisms Acting Remotely To Limit Excitation and Seizure Smentioning
confidence: 99%
“…injection of an equal mixture of ketamine hydrochloride (80 mg/kg, Troy Laboratory PTY Limited Glendenning, NSW, Australia) and xylazine hydrochloride (20 mg/kg, Troy Laboratory PTY Limited Glendenning, NSW, Australia). To lesion the nigrostriatal pathway, the heads of the animals were shaved and placed into a Stoelting stereotaxic frame and a unilateral hole on the right side of the skull was made as described before [ 67 ], aiming at the striatum. The rats received unilateral injections of 6-OHDA at three distinct locations within the caudate-putamen (7 µg in each site).…”
Section: Methodsmentioning
confidence: 99%